Mineral matters content in the organs of the species Quercus frainetto and Quercus cerris in the ass. Quercetumfrainetto-cerris macedonicum Oberd. 1948, em. Horvat 1959 in „Galičica,, National Park - Mulev, Milto; Grupče, Ljupčo; Melovski, Ljupčo; Derlieva, Lidija (Macedonian Journal of Ecology and Environment, 1994)
The content of the bioelements in the organs of woody plants Quercus frainetto and Quercus cerris in the macedonian oak ecosystem Quercetumfrainetto-cerris macedonicum was studied. The total quantity of the following bioelements: N, Ca, K, P, Fe, Mg, Mn and Na in these plants, per hectare area, was 3645,76 kg.